Superior vena cava syndrome: a comprehensive review - Sasikumar, Aswin; Kothiwale, V. A. (International Journal of Research in Medical Sciences, 2025)
Superior vena cava syndrome (SVCS) is a condition resulting from obstruction or compression of the superior vena cava, leading to venous congestion of the head, neck, and upper extremities. This review provides a comprehensive discussion on the etiology, pathophysiology, clinical presentation, diagnostic approach, and management strategies for SVCS. Advances in imaging and endovascular interventions have improved the diagnosis and treatment of SVCS. Although malignancies remain the leading cause, benign etiologies have gained significance in the modern era. Despite these advancements, the treatment of SVCS remains challenging, requiring a multidisciplinary approach.